2007
DOI: 10.1038/sj.ejcn.1602623
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of partially hydrolyzed guar gum on transitory diarrhea induced by ingestion of maltitol and lactitol in healthy humans

Abstract: Objectives: To estimate the suppressive effect of partially hydrolyzed guar gum (PHGG) on transitory diarrhea induced by ingestion of a sufficient amount of maltitol or lactitol in female subjects. Design: The first, the minimal dose level of maltitol and lactitol that would induce transitory diarrhea was estimated separately for each subject. Individual subject was administered a dose that increased by 5 g stepwise from 10 to 45 g until diarrhea was experienced. Thereafter, the suppressive effect on diarrhea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…The SCF (1989) described the laxation caused by osmotic pressure as "osmotic diarrhoea", in order to differentiate it from the term "diarrhoea" which is commonly used to describe a gastro-enteric sickness. Maltitol and lactitol have been described as inducing transitory osmotic diarrhoea in humans by the hyperosmotic retention of fluids in the small and large intestines at doses down to 15 g (Nakamura et al, 2007). Upon regular consumption of maltitol and other polyols (daily for two 9-day periods), the occurrence of an intestinal adaptation to maltitols laxative effect at doses of up to 30 g has been reported in some individuals (Brommage et al, 1993;Ruskoné-Fourmestraux et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The SCF (1989) described the laxation caused by osmotic pressure as "osmotic diarrhoea", in order to differentiate it from the term "diarrhoea" which is commonly used to describe a gastro-enteric sickness. Maltitol and lactitol have been described as inducing transitory osmotic diarrhoea in humans by the hyperosmotic retention of fluids in the small and large intestines at doses down to 15 g (Nakamura et al, 2007). Upon regular consumption of maltitol and other polyols (daily for two 9-day periods), the occurrence of an intestinal adaptation to maltitols laxative effect at doses of up to 30 g has been reported in some individuals (Brommage et al, 1993;Ruskoné-Fourmestraux et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…También se ha estudiado el uso de la GGPH en la diarrea no asociada a nutrición enteral, encontrándose resultados positivos en pacientes con diarrea severa por cólera, si bien es difícil determinar la dosis óptima en este tipo de pacientes (46); y en la diarrea transitoria inducida por maltitol o lactitol en mujeres (47).…”
Section: Estreñimiento Y Diarrea No Asociada a Nutrición Enteralunclassified
“…The sample was eluted with deionized distilled water at a flow rate of 1.0 mL/min and the injection volume of the sample was 5 L. Calculation and statistical analysis. We used the chisquare test to compare the percentage of the subjects whose osmotic diarrhea was improved by ingesting cellulose, PHA-Na or PHGG ( 9 ). The amount of maltitol remaining in the rat stomach and the amount being transferred to the small intestine at each time point after administration were calculated in terms of means and standard deviations (SD), and we compared the amount among the maltitol group, the maltitol and cellulose group, and the maltitol and PHA-Na group using ANOVA and Tukey's post hoc test.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we reported that the addition of 5 and 10 g of partially hydrolyzed guar gum (PHGG) to the minimal dose level of maltitol that induced osmotic diarrhea (MMD) suppressed diarrhea in 23 out of 28 subjects (82.1%) ( 9 ). In addition, PHGG improved the diarrhea caused by tube feeding of enteral nutrition in the elderly ( 10 , 11 ) and treated acute diarrhea with infection in children ( 11 , 12 ).…”
mentioning
confidence: 99%